Perencanaan Ulang Struktur Bangunan Gedung Training Center (Jalan Durian Raya, Banyumanik Semarang) - Perkasa, Febry Candra; Messara, Hugo; Widianto, David; Setiadi, Budi (Universitas Katolik Soegijapranata Semarang, 2024)
Building is one of the places used for student activities both for entertainment, lectures to work, especially in major cities.This building is functioned as a Training Center for students and lecturers. Building with a height of 32 meters with 8 floors and 1 roof floor with a land area of 3192 m2 and a building area of 5616 m2. The building has a shearwall in the directions of x and in the central of structure.A structure of training center building use indonesian code SNI 1726:2019, SNI 2847:2019, SNI 1727:2019, PBI 1971and PPURG. Planning of the lower structure includes the foundation, pilecaps, and tiebeam. While planning of the upper structure includes beam, column, floor plates, stairs, and shearwall. To calculate the moments and reactions to the building using ETABS version 16.The result of planning floor slabs and roof slabs with a thickness of 13 cm. Beam design planning BI-A = 350 x 700, BI-B = 250 x . 500 , BA = 200 x 300. Column planning design K1 = 500 x 500, K2 = 450 x 450, K3 = 400 x 400, K4 = 350 x 350. Design planning of pile foundation 30 cm with a depth of 20 meters.